Isomerizing hydroformylation of cashew nut shell liquid - Pandey, Swechchha; Shinde, Dinesh R.; Chikkali, Samir H. (ChemCatChem, 2017)
A small library of bisphosphorus ligands was evaluated in the rhodium-catalyzed isomerizing hydroformylation (I-HF) of cashew nut shell liquid (CNSL). The rhodium complex of 1,2-bis((di-tert-butylphosphanyl)methyl)benzene (BDTBPMB; L4) outperformed the other bisphosphite and bisphosphine ligands and unveiled a moderate selectivity of 28% and 50% in the I-HF of CNSL monoene and methoxy-protected monoene, respectively. The resultant aldehyde 16-(3-methoxyphenyl)hexadecanal P1 was isolated and its identity was fully established. Application of bis-phosphine ligand L4 in the I-HF of highly challenging CNSL cardanol (S3) and methoxy-protected CNSL cardanol yielded a linear selectivity of 74%, although with reduced conversion. To demonstrate the synthetic utility of our strategy, the obtained aldehyde (derived from S3) was subjected to hydrogenation and the resultant 3-(16-hydroxyhexadecyl) phenol (P8) was isolated in 89% isolated yield. High-pressure NMR investigation revealed selective formation of a bis-equatorial BDTBPMB-rhodium complex, which might be responsible for the excellent linear selectivity.

Imido-P(V) trianion supported enantiopure neutral tetrahedral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Paithankar, Harshad; Chugh, Jeetender; Steiner, Alexander; Boomishankar, Ramamoorthy (Chemical Communications, 2018)
Charge-neutral chiral hosts are attractive due to their ability to recognize a wide range of guest functionalities and support enantio-selective processes. However, reports on such charge-neutral cages are very scarce in the literature. Here, we report an enantiomeric pair of tetrahedral Pd(II) cages built from chiral tris(imido) phosphate trianions and oxalate linkers, which exhibit enantioselective separation capabilities for epichlorohydrin, beta-butyrolactone, and 3-methyl- and 3-ethyl cyclopentanone.

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.